Decompensated Liver Failure and Acute Renal Failure in a Patient with Chronic HBV,HCV, and HIV Infections - Devesh Sharma; Saumya Singh; Brijnandan Singh; Nandlal Kumar; Rajan Pathak (International Journal of Pathogens, 2024)
This case study focuses on a 30-year-old male patient suffering from decompensated liver failure and acute renal failure, complicated by chronic hepatitis B (HBV), hepatitis C (HCV), and HIV/AIDS. Presenting with severe abdominal pain, nausea, and general weakness, the patient had a history of alcohol and intravenous drug use, leading to chronic liver disease and acute renal failure. Despite aggressive interventions, including intravenous antibiotics and fluid therapy, his condition worsened rapidly, leading to his transfer to the ICU and eventual death. The case emphasizes the complex interplay between HBV, HCV, and HIV infections. The patient’s liver failure, compounded by hepatorenal syndrome—a functional renal impairment commonly seen in advanced liver disease—created significant clinical challenges. Furthermore, HIV's immunosuppressive effects accelerated liver disease progression and complicated management due to potential drug interactions. Key laboratory findings included elevated liver enzymes, indicating significant liver damage, and severe anemia, likely worsened by gastrointestinal bleeding due to portal hypertension. Kidney function was severely impaired, as reflected by elevated serum creatinine and blood urea nitrogen levels, alongside hyperkalemia. This report highlights the critical need for a multidisciplinary approach involving hepatologists, nephrologists, infectious disease specialists, and critical care teams in managing patients with multiple chronic infections. The patient’s rapid deterioration underscores the importance of early diagnosis, aggressive treatment, and comprehensive care plans tailored to the complex needs of such high-risk individuals to improve outcomes.
Keywords: Acquired immunodeficiency syndrome (AIDS); Hepatitis A; Hepatitis B; Human immunodeficiency virus (HIV); diagnosis